Quality of life and self-image in patients with head and neck cancer - Silveira e Silva, Marina; Universidade do Vale do Rio dos Sinos (Pontificia Universidad Javeriana, 2010)
Head and neck cancer refers to skin tumors that affect people of all ages. Treatments for this type of disease include surgeries, chemotherapy and radiotherapy. Purpose: to examine self-image and quality of life of patients who had head and neck cancer. Participants: 28 patients between 30 - 73 years. Instruments: Instrument for Assessing Quality of Life of the WHO - and the brief version of Evaluation Scale with Body Satisfaction. Results: Total quality of life and their subscales was positively correlated with self-image, exception of social relations subscale. Self-image was a significant predictor of total quality of life and physical psychological and environment dimension. Conclusion: quality of life was closely linked with self-image in these patients